Books, Read-Alouds, and Voluntary Book Interactions: What Do We Know About Centers Serving Three-Year-Olds?. Issue 2 (3rd April 2018) - Mesmer, Heidi Anne
ABSTRACT: This study examined the quality of books, the quality of read-alouds, and children's voluntary interactions with books in childcare centers serving low-income 3-year-olds ( N  = 30). Although a large percentage of centers had book areas, the features of book areas differed. The highest percentage of books was highly recommended and appropriate (39%) but about 14% was completely inappropriate. Childcare personnel managed read-alouds well and involved children. The bulk of naturally occurring talk focused on reviewing story content (39.78%) with management/task organization following (27%). Three-year-olds did not voluntary interact with books at very high levels. Comparisons of the findings to existing studies suggest trends.